Emotion Recognition in Human-Machine Interaction and a Review in Interpersonal Communication Perspective - Vimala, Govindaraju; Dhanabalan, Thangam (IGI Global, 2024)
Emotions are fundamental to daily decision-making and overall wellbeing. Emotions are psychophysiological processes that are frequently linked to human-machine interaction, and it is expected we will see the creation of systems that can recognize and interpret human emotions in a range of ways as computers and computer-based applications get more advanced and pervasive in people's daily lives. Emotion recognition systems are able to modify their responses and user experience based on the analysis of interpersonal communication signals. The ability of virtual assistants to respond emotionally more effectively, the ability to support mental health systems by identifying users' emotional states, and the enhancement of human-machine interaction applications. The aim of this chapter is reviewing the interpersonal communication elements of the emotional interaction models that are now.